Do you have what your customers want?: An empirical study of telecommunication companies websites - Ab Hamid, Noor Raihan; Ahmad, Fauziah; Tahir Shah, Saharbudin Naim; Arshad, Noor Habibah (2010)
The emergence of Electronic Commerce (ecommerce) has brought tremendous yet significant changes to businesses particularly due to globalization pressure. More brick and mortar companies believe in the significant value of Internet-based transactions and realize the importance of doing businesses over the Internet. Companies realize the advantages of using the Internet for making online transactions especially for cost reduction and also improved customers’ satisfaction. Electronic customer relationship management (eCRM) features are among the main factors that contribute to the success of any ecommerce Web sites.E-CRM programmes and implementations should focus on effectiveness of managing customer relations on the Internet through effective use of Internet features either to deliver updated and accurate information, allowing customer services support and providing personalized and value-added services. Thus, the aims of this research are to identify E-CRM features available on telecommunication Websites and customers’ perceived importance of these features. The primary data for this research was collected through a questionnaire survey. The findings from this research showed that from the nine determinants identified, ease of use was ranked the most important feature in E-CRM. We discuss the limitations of this study and future directions of research.